2023
DOI: 10.3389/fimmu.2023.1178188
|View full text |Cite
|
Sign up to set email alerts
|

Effect and mechanism of chlorogenic acid on cognitive dysfunction in mice by lipopolysaccharide-induced neuroinflammation

Abstract: BackgroundNeuroinflammation is an important factor causing numerous neurodegenerative pathologies. Inflammation can lead to abnormal neuronal structure and function and even death, followed by cognitive dysfunction. There is growing evidence that chlorogenic acid has anti-inflammatory effects and immunomodulatory activity.PurposeThe aim of this study was to elucidate the potential targets and molecular mechanisms of chlorogenic acid in the treatment of neuroinflammation.MethodsWe used the lipopolysaccharide-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Mitochondrial dysfunction is a critical initiator of dopaminergic neuronal degeneration and is intimately linked with PD. , This dysfunction often results from the inhibitory effects of abnormal α-synuclein and toxins like MPTP on mitochondrial complex I of the electron transport chain . MPTP, being lipophilic, crosses the blood–brain barrier and is converted to toxic MPP + in glial cells, impeding complex I, disrupting electron flow, reducing ATP production, and generating ROS, thereby creating a feedback loop that escalates oxidative stress. Importantly, mitochondrial dysfunction also plays a significant role in activating the NLRP3 inflammasome .…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction is a critical initiator of dopaminergic neuronal degeneration and is intimately linked with PD. , This dysfunction often results from the inhibitory effects of abnormal α-synuclein and toxins like MPTP on mitochondrial complex I of the electron transport chain . MPTP, being lipophilic, crosses the blood–brain barrier and is converted to toxic MPP + in glial cells, impeding complex I, disrupting electron flow, reducing ATP production, and generating ROS, thereby creating a feedback loop that escalates oxidative stress. Importantly, mitochondrial dysfunction also plays a significant role in activating the NLRP3 inflammasome .…”
Section: Discussionmentioning
confidence: 99%
“…Fernández et al analyzed the effect of rutin on sleep time and sedative action through thiopental-induced sleep test and behavioral analysis and reported on the possibility of use as a sleep-promoting material [42]. Previous studies have shown that subacute ingestion of chlorogenic acids decreased sleep latency in clinical trials [43], and in vitro and in vivo studies have reported that it prevents cognitive decline and nerve damage through tumor necrosis factor (TNF) and nuclear factor erythroid 2 related factor 2 (Nrf2)-nuclear factor kappa-light-chain-enhancer of activated B (NF-κB) signaling pathways [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…The potential contributive mechanism was Nrf2/PPAR activation [235]. CGA attenuates the polarization of macrophages and alleviates cognitive impairments in an LPS-induced neuroinflammation mouse model by targeting the TNFα signaling pathway [236]. CGA improves memory dysfunction and attenuates frontal cortex inflammation in diabetic rats [237].…”
Section: Mitigative Effects On Parkinson's Disease (Pd) (Figurementioning
confidence: 99%
“…Mouse model of anxiety [234]; sleep-deprived mice activation [235]; LPS-induced neuroinflammation mouse model [236]; diabetic rats [237]; corticosterone-induced depression-like mice [238] Activation of Nrf2/PPAR [235]; inhibition of the TNFα signaling pathway [236] CGA Healthy subjects with mild cognitive impairment [269][270][271]; healthy subjects observed [272,273] n.a. CGA; CGA-enriched coffee berry extracts Neuropathic pain (Section 6.6)…”
Section: Inflammation and Oxidationmentioning
confidence: 99%